Pengaruh Konsentrasi Pupuk Plant Catalys 2006 dan Jarak Tanam Terhadap Pertumbuhan dan Produksi Tanaman Terung (Solanum melongena L.) - Winda Isdianti; Tutik Nugrahini; Mahdalena Mahdalena (Universitas Widya Gama Mahakam, 2016)
Concentrations of Catalys Award Fertilizer Plant 2006 and Plant Spacing on the Growth and Production of Eggplant (Solanum melongena L.). The aim of research to determine the exact concentration of the fertilizer plant catalys 2006, so as to provide maximum results, to determine the proper spacing of the plants of eggplant and to understand the interaction on the eggplant plants to fertilization and plant spacing. This study was conducted over five months, ie from May and October 2015. The study in the village Manunggal Tenggarong District Seberang Jaya Regency. This study uses a randomized block design with 4 x 3 factorial experiment consisting of three replications. The first factor is a plant fertilizer catalys 2006, which consists of 4 levels: namely p0 (without treatment), p1 (3g / 1liter water), p2 (5g / 1liter water), p3 (7g / 1 liter of water). The second factor is a spacing consists of three levels ie t1 (70cm x 70cm), t2 (70 cm x 80), t3 (70 x 90). The results showed that fertilizer treatment plant catalys 2006 did not significantly affect plant height, stem diameter, number of branches, number of fruits per plant and fruit length, but the real impact on the weight of fruit per plant that is the highest weight of the fruit crops 360.27 g with treatment p2 (5 g / liter of water) and fruit weight per plot is 2161.60 g, equivalent to 86.46 Kw ha-1 with a treatment p2 (5 g / liter of water). While the spacing of no significant effect on all parameters observed. There is no interaction between the fertilizer plant catalys 2006 and spacing of the growth and yield of eggplant.